The double-edged sword of cultural distance in international acquisitions - Reus, Taco H; Lamont, Bruce T (Journal of International Business Studies, 2009)
This study aims to bring together seemingly contradicting arguments in the literature about the role of cultural distance in international acquisitions. We offer a model that postulates that cultural distance relates negatively to international acquisition performance because it taxes integration capabilities during international acquisitions, but that cultural distance also elevates the positive association of integration capabilities and international acquisition performance because it provides more learning opportunities that can only be exploited with strong integration capabilities. Empirical tests with a sample of international acquisitions by 118 US multinational companies provide support for the proposed model. On one hand, we find that cultural distance impedes understandability of key capabilities that need to be transferred, and constrains communication between acquirers and their acquired units, bringing about a negative indirect effect on acquisition performance. On the other hand, we find that cultural distance enriches acquisitions by enhancing the positive effects of understandability and communication on acquisition performance. Acquirers that can overcome the impeding effects of cultural distance on understanding key capabilities and effective communication appear to reap significant performance gains. Our study provides initial support for a double-edged sword effect of cultural differences on acquisition performance, and illustrates the importance of integration capabilities.